The Torah Ark in Renaissance Poland : a Jewish Revival of Classical Antiquity. - Rodov, Ilia M. (Jewish and Christian perspectives series., 2013)
The book explores the patronage, formation, and symbolism of the Renaissance Torah ark in Polish synagogues.